Clinical Efficacy Assessment Of Antiviral-Antibiotic Combination Therapy For Prevention Of Complications Associated With Severe Influenza Infection - Ishaqui, Azfar Athar (2021)
Secondary bacterial infections, mechanical respiratory support, and multi-organ failure are the complications associated with severe Influenza infection responsible for the mortalities and morbidities worldwide. The use of antibiotics in viral influenza infection is still debatable. The current study aimed to compare the efficacy of Antiviral drug therapy alone and Antiviral-Antibiotic combination therapy in prevention of complications associated with Influenza infection hospitalized patients. This two-center, retrospective cohort study was conducted in two tertiary care teaching hospitals in Saudi Arabia. Laboratory confirmed Influenza-A (non-H1N1), Influenza-B, Influenza-A (H1N1) hospitalized patients who presented in the emergency room after 48 hours of symptoms onset were identified and divided into two groups; Group-1 patients were initiated on Antiviral alone drug therapy while Group-2 patients were initiated on Antiviral-Antibiotic combination therapy. Both group patients were evaluated for different clinical outcomes, such as incidences of influenza associated secondary bacterial infections, the need for respiratory support, length of hospitalization stay, incidences of multi-organ failure, early clinical failure, and time to clinical stability. Comparative efficacy analysis of Antiviral alone therapy patients vs. Antiviral-Antibiotic combination therapy patients for Influenza-A (non-H1N1) strain (212 vs. 187 patients), Influenza-B (153 vs. 131 patients), and Influenza-A (H1N1) strain (227 vs. 286 patients) revealed that incidences of secondary bacterial infection, need of respiratory support, incidences of ICU admission, length of hospitalization stay and time to clinical stability was statistically significant less for patients initiated on Antiviral-Antibiotic combination therapy for all three Influenza strains.